2009
DOI: 10.1117/12.812460
|View full text |Cite
|
Sign up to set email alerts
|

Nonrigid correction of interleaving artefacts in pelvic MRI

Abstract: This paper presents a novel method to reduce the effects of interleaving motion artefacts in single-plane MR scanning of the pelvic region without the need for k-space information. Interleaved image (or multipacket) acquisition is frequently used to reduce cross-talk and scanning time during full pelvic MR scans. Patient motion during interleaved acquisition can result in non-linear "staircase" imaging artefacts which are most visible on sagittal and coronal reconstructions. These artefacts can affect the segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…While all projects aim to improve patients’ experience, two in particular — reducing waiting times at emergency departments through better resource planning, 17 and improving radiotherapy treatment for prostate 15 and brain cancer — fulfil this aim.…”
Section: Project Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While all projects aim to improve patients’ experience, two in particular — reducing waiting times at emergency departments through better resource planning, 17 and improving radiotherapy treatment for prostate 15 and brain cancer — fulfil this aim.…”
Section: Project Resultsmentioning
confidence: 99%
“…The MILXview platform is also being used to improve radiotherapy treatment planning for prostate cancer 15 and cancers of the brain. https://doi.org/10.5694/j.1326-5377.2011.tb02939.x describe an alternative treatment planning method for prostate cancer.…”
Section: Research Capabilities and Projectsmentioning
confidence: 99%
“…Probabilistic atlas‐based organ segmentation methods were developed to automatically segment the organs of interest (prostate, rectum, bladder, and femoral heads) from the MRI scans. After the scans were preprocessed (including correction of intensity inhomogeneity 8 and patient movement artefacts 9 ), the images and manually defined contours for each patient were combined into a single reference atlas by image registration methods. This atlas can then be warped onto the MRI scans of a new patient, automatically contouring the organs of interest (Box 3).…”
Section: Patients and Feasibility Study Designmentioning
confidence: 99%
“…For instance, in two-packet MRI, all the even slices (termed 'even volume') are acquired first before the odd slices (termed 'odd volume') are obtained. Then the reconstructed MR images are vulnerable to motion artifacts due to subject movements during interleaved sequences [2]. This may result in mis-alignments among the acquired packets, which can be easily detected in sagittal and coronal views.…”
Section: Introductionmentioning
confidence: 99%
“…They used a Kaiser-Bessel function for interpolating missing data during the reconstruction process. Dowling et al [2] suggested the non-rigid correction of interleaving artifacts in pelvic MRI. Most of these methods have a similar algorithmic framework; in that they use registration for motion estimation.…”
Section: Introductionmentioning
confidence: 99%